Abdominal obesity and white matter microstructure in midlife. Issue 7 (8th April 2017) - Birdsill, Alex Cole; Oleson, Stephanie; Kaur, Sonya; Pasha, Evan; Ireton, Adele; Tanaka, Hirofumi; Haley, Andreana
Abstract: The aging U.S. population and the recent rise in the prevalence of obesity are two phenomena of great importance to public health. In addition, research suggests that midlife body mass index (BMI) is a risk factor for dementia, a particularly costly disease, in later life. BMI could influence brain health by adversely impacting cerebral white matter. Recently, greater BMI has been associated with lower white matter fractional anisotropy (FA), an index of tissue microstructure, as measured by diffusion‐tensor imaging in midlife. The aim of this study was to investigate the role of abdominal obesity, the most metabolically active adipose tissue compartment, and white matter microstructure in midlife. Community dwelling participants ( N  = 168) between the ages of 40–62 underwent MRI scanning at 3T and a general health assessment. Inferences were made on whole brain white matter tracts using full‐tensor, high‐dimension normalization, and tract‐based spatial statistics. Higher waist circumference was associated with higher FA, indicating more directional diffusion in several white matter tracts controlling for age, sex, triglycerides, systolic blood pressure, fasting glucose, and HDL‐cholesterol. Post hoc analysis revealed that greater waist circumference was associated with lower axial diffusivity, indicating lower parallel diffusion; lower radial diffusivity, indicating lower perpendicular diffusion; and lower mean diffusivity, indicating restricted diffusion. This is the first study to report a positive relationship between obesity and FA, indicating a more complicated view of this relationship in the aging brain. Hum Brain Mapp 38:3337–3344, 2017 . ©2017 Wiley Periodicals, Inc.